1966
DOI: 10.1128/jb.91.3.963-966.1966
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Diseases in Wild Animals in Utah VI. Experimental Infection of Birds with Rickettsia rickettsii

Abstract: HASKELL. Infectious diseases in wild animals in Utah. VI. Experimental infection of birds with Rickettsia rickettsii. J. Bacteriol. 91:963-966. 1966.-Chickens, pigeons, pheasants, sparrow hawks, red-tailed hawks, ravens, magpies, and a marsh hawk were inoculated with Rickettsia rickettsii, the etiological agent of Rocky Mountain spotted fever. The development and persistence of complement-fixing (CF) antibodies and rickettsemias were tested for in these birds. Rickettsiae were recovered from the blood of a num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

1972
1972
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 2 publications
1
8
0
1
Order By: Relevance
“…11 , with bacteremia lasting from 5 to 11 DPI (6 days) in capybaras exposed by intraperitoneal inoculation. In addition, similar extents (8-12 days) were registered in diverse studies with other rodent species in the United States 9,32 . In contrast, this bacteremic period is shorter than the 26 days reported for the opossum Didelphis aurita in Brazil 10 , or the 4 week-period reported for Didelphis virginiana in the United States 33 .…”
Section: Infected Capybarassupporting
confidence: 68%
“…11 , with bacteremia lasting from 5 to 11 DPI (6 days) in capybaras exposed by intraperitoneal inoculation. In addition, similar extents (8-12 days) were registered in diverse studies with other rodent species in the United States 9,32 . In contrast, this bacteremic period is shorter than the 26 days reported for the opossum Didelphis aurita in Brazil 10 , or the 4 week-period reported for Didelphis virginiana in the United States 33 .…”
Section: Infected Capybarassupporting
confidence: 68%
“…For example, one may (rightly) be forbidden to infect wild animals experimentally. A possible exception would be to add ecoimmunological analysis onto epidemiological susceptibility studies such as those used to assess the potential for wild hosts to sustain transmission of zoonotic infections such as rickettsia, brucellosis, or monkeypox (Lundgren & Thorpe 1966a;Lundgren, Thorpe & Haskell 1966b;Xiao et al 2005;Nol, Olsen & Rhyan 2009).…”
Section: E S I G N S 2 -4 : E X P E R I M E N T S I N W H I C H I Nmentioning
confidence: 99%
“…19 This last requirement is very important if one considers that once living in an endemic area, each individual host will develop only one rickettsemia (lasting for a few days or weeks) during its lifetime, since after the rickettsemia, the animal develops strong immunity against the agent, precluding a second rickettsemia. 20,21 In Brazil, at least two animals are incriminated to act as efficient amplifier hosts for A. cajennense: capybaras and opossums (Didelphis spp.). Capybaras are abundant and act as primary hosts for A. cajennense in all RMSFendemic areas of the state of São Paulo, where A. cajennense is the vector, in contrast to many other non-endemic areas for RMSF with abundant populations of A. cajennense sustained by horses in the absence of capybaras.…”
Section: Introductionmentioning
confidence: 99%
“…29 This has been the longest rickettsemic period ever reported for R. rickettsii infection; other animals develop rickettsemia usually lasting for 1 to 2 weeks. 18,20 Opossums are also prolific, the female births 5 to 9 young between 1 and 3 times per year. Finally, a recent study in our laboratory has shown that R. rickettsii-experimentally-infected opossums (Didelphis aurita) developed rickettsemia lasting for 3 to 4 weeks, when ∼5-20% of the A. cajennnense immature ticks that fed on them became infected by R. rickettsii, as shown by PCR performed on the ticks after molting.…”
Section: Introductionmentioning
confidence: 99%